Effect of Different Nickel Percentage in Solder Alloy towards Intermetallic Compound Formation and Growth - Muhammad Asyraf, Abdullah; Siti Rabiatull Aisha, Idris (IOP Publishing, 2021)
The growth of electronics product has increased rapidly and hence drive challenges among the designers as well as manufacturers to select the best electronic packaging materials for their products. Among those materials, lead free solders has become the best replacement for lead-containing solders even though its performance still could not meet the original specification. Thus, this paper is aiming at studying the effect Nickel (Ni) additional with difference percentage into solder alloy toward intermetallic compound formation (IMC) and growth at the interface of the solder joint. The work was carried out by producing Sn-xNi (x = 0.0, 0.3, 0.5, 0.7, 1.0) through powder metallurgy method. The process started with powder milling at the speed of 1400 rpm for 3 hours. Then it was compacted into a thin pallet with size of 6mm diameter at the pressure of 5 ton. After that, the sample were subjected to reflow soldering for 250˚C for 25min heating duration and 15min holding time. Solder joint strength was carried out using ASTM D1002. Finally, characterisation was made in terms of IMC morphology, thickness and solder joint strength using metallographic microscope as well as scanning electron microscopy-energy dispersive x-ray (SEM-EDX). Results showed that the addition of Ni with different percentage produced different morphology of IMC at the interface after reflow soldering which also affects its growth behaviour. The IMC's formed after reflow soldering produced closed and packed grain boundary when solder with higher Ni content was used. The type of IMC formed at the solder joint was Cu6Sn5 and its thickness increased with Ni addition. These results were the proof that Ni is a good candidate to improve solder joint performance by restricting the formation and growth of Cu3Sn IMC. In addition, the solder joint strength was found to be increasing upon Ni percentage increment. The highest strength value of 5.885MPa was produce when Ni was added up to 1.0%. This showed that Ni not only a good candidate to improve joint performance in IMC formation but also help in strengthening the solder joint.